Factors influencing medical students in a lower-middle income country to consider psychiatry as a career option - Agyapong, Vincent I. O.; Shalaby, Reham; Agyapong-Opoku, Gerald (Frontiers in Medicine, 2025)
ObjectiveTo assess and identify the environmental, curriculum, teaching related factors and preconception about psychiatry that influence medical students’ attitudes toward psychiatry careers after completing psychiatry rotations.MethodsThis is a cross-sectional study involving fifth- and sixth-year medical students of four public medical schools in Ghana. Data was analyzed using chi-square test and logistic regression analysis.ResultsOut of 1,041 clinical year medical students from the four public medical schools in Ghana, 475 students completed survey forms and provided responses related to their preference for a psychiatry career following the completion of a clinical rotation, yielding a response rate of (45.63%). Medical students who were identified as female (OR = 1.55; 95% CI: 1.01–2.35), were in their sixth year (OR = 1.65; 95% CI: 1.06–2.58), had diaspora-based psychiatrists participate in their clinical training (OR = 1.7; 95% CI: 1.10–2.62), and had considered psychiatry careers before undertaking psychiatry clinical rotation (OR = 3.19; 95% CI: 1.73–5.87) were more likely to consider psychiatry as a future career after completing a psychiatric rotation, when compared to their respective counterparts.ConclusionDiverse factors have affected students’ consideration of psychiatry as a future career. Health policy makers and health training institutions in low- and middle-income countries should consider designing programs that will impact positively on the preconceptions of medical students about psychiatry careers in addition reaching out to human resources abroad from within their nationals, particularly if these resources exist.